Evaluation of inflammatory markers in patients with confirmed bacterial infection according to the type of isolated pathogen - Jelena Micik; Evgenija Mihajloska; Aleksandar Dimkovski; Georgina Gorgieva Atanasova; Aleksandar Dimovski; Ljubica Shuturkova; Zoran Sterjev; Aleksandra Grozdanova (Makedonsko Farmacevtski Bilten)
Frequent bacterial infections in intensive care demand routine microbiological screening and antimicrobial management to effectively address potential Gram-positive and Gram-negative pathogens causing post-surgical infections. This study aimed to assess whether serum levels of leukocytes, C-reactive protein, and procalcitonin — biomarkers commonly used in daily clinical practice to predict postoperative outcomes — differ between infections caused by Gram-positive or Gram-negative bacteria in adult patients admitted to a cardiac surgical intensive care unit (CICU), in order to support treatment decisions. Laboratory data were retrospectively collected from 564 adult patients who underwent cardiac surgery and were admitted to the cardiac surgical intensive care unit of the Cardiac Surgery Department at Acibadem Sistina Clinical Hospital. Data included serum leukocyte levels recorded on the day a positive microbiological result was obtained and over the subsequent four days. C-reactive protein and procalcitonin levels were measured starting from the day of pathogen isolation and continued for 48 and 72 hours, respectively. The study population was divided into two groups: Group 1, consisting of patients with isolated Gram-positive microorganisms, and Group 2, consisting of patients with isolated Gram-negative microorganisms. Both groups showed a progressive reduction in leukocyte levels, with no significant differences in clinical presentation and no statistical differences in C-reactive protein and procalcitonin levels between Gram-positive and Gram-negative infections. Our findings support the conclusion that monitoring the levels of inflammatory markers, regardless of whether the microorganisms are Gram-positive or Gram-negative, is essential for guiding treatment de-escalation.